Partial Inhibition of Glycolysis Reduces Atherogenesis Independent of Intraplaque Neovascularization in Mice. Issue 5 (May 2020) - Perrotta, Paola; Van der Veken, Bieke; Van Der Veken, Pieter; Pintelon, Isabel; Roosens, Laurence; Adriaenssens, Elias; Timmerman, Vincent; Guns, Pieter-Jan; De Meyer, Guido R.Y.; Martinet, Wim
Abstract : Objective: Intraplaque neovascularization is an important feature of unstable human atherosclerotic plaques. However, its impact on plaque formation and stability is poorly studied. Because proliferating endothelial cells generate up to 85% of their ATP from glycolysis, we investigated whether pharmacological inhibition of glycolytic flux by the small-molecule 3PO (3-[3-pyridinyl]-1-[4-pyridinyl]-2-propen-1-one) could have beneficial effects on plaque formation and composition. Approach and Results: ApoE −/ − (apolipoprotein E deficient) mice treated with 3PO (50 µg/g, ip; 4×/wk, 4 weeks) showed a metabolic switch toward ketone body formation. Treatment of ApoE −/− Fbn1 C1039G+/− mice with 3PO (50 µg/g, ip) either after 4 (preventive, twice/wk, 10 weeks) or 16 weeks of Western diet (curative, 4×/wk, 4 weeks) inhibited intraplaque neovascularization by 50% and 38%, respectively. Plaque formation was significantly reduced in all 3PO-treated animals. This effect was independent of intraplaque neovascularization. In vitro experiments showed that 3PO favors an anti-inflammatory M2 macrophage subtype and suppresses an M1 proinflammatory phenotype. Moreover, 3PO induced autophagy, which in turn impaired NF-κB (nuclear factor-kappa B) signaling and inhibited TNF-α (tumor necrosis factor-alpha)–mediated VCAM-1 (vascular cell adhesion molecule-1) and ICAM-1 (intercellular adhesion molecule-1) upregulation. Consistently, a preventive 3PO regimen reduced endothelial VCAM-1 expression in vivo. Furthermore, 3PO improved cardiac function in ApoE −/− Fbn1 C1039G+/− mice after 10 weeks of treatment. Conclusions: Partial inhibition of glycolysis restrained intraplaque angiogenesis without affecting plaque composition. However, less plaques were formed, which was accompanied by downregulation of endothelial adhesion molecules—an event that depends on autophagy induction. Inhibition of coronary plaque formation by 3PO resulted in an overall improved cardiac function. Abstract : Supplemental Digital Content is available in the text.